Analysis of the Global Banking Network by Random Matrix Theory - Namaki, Ali; Raei, Reza; Ardalankia, Jamshid; Hedayatifar, Leila; Hosseiny, Ali; Haven, Emmanuel; Jafari, G. Reza (Frontiers in Physics, 2021)
Since the financial crisis of 2008, the network analysis of financial systems has attracted a lot of attention. In this paper, we analyze the global banking network via the method of Random Matrix Theory (RMT). By applying that method on a cross border lending network, it is shown that whilst the connectivity between different parts of the network has risen and the profile of transactions has diversified, the role of hubs remains important in the weighted perspective. The largest eigenvalue of the transaction matrix as the leading mode of the system shows sharp growth since 2002. As well, it is observed that its growth has diminished since 2008. This indicates that the crisis of 2008 has left a long-lasting footprint on the financial system. Analyzing the mean value of the participation ratio reveals the fact that the role of countries in forming small modes, has increased since 2002. In our final analysis, we provide snapshots of the hubs in the network over time. We observe that the share of countries in total transactions is not equal to their share in shaping the eigenvector of the largest eigenvalue. In 2018 for example, whilst the UK leads the share of transactions, it is the US which has the the largest value in the leading eigenvector. The proposed technique in the paper can be useful for analyzing different types of interaction networks between countries.